If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.4(3x + 6) = 1.3 + -1(x + 2) Reorder the terms: 0.4(6 + 3x) = 1.3 + -1(x + 2) (6 * 0.4 + 3x * 0.4) = 1.3 + -1(x + 2) (2.4 + 1.2x) = 1.3 + -1(x + 2) Reorder the terms: 2.4 + 1.2x = 1.3 + -1(2 + x) 2.4 + 1.2x = 1.3 + (2 * -1 + x * -1) 2.4 + 1.2x = 1.3 + (-2 + -1x) Combine like terms: 1.3 + -2 = -0.7 2.4 + 1.2x = -0.7 + -1x Solving 2.4 + 1.2x = -0.7 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 2.4 + 1.2x + x = -0.7 + -1x + x Combine like terms: 1.2x + x = 2.2x 2.4 + 2.2x = -0.7 + -1x + x Combine like terms: -1x + x = 0 2.4 + 2.2x = -0.7 + 0 2.4 + 2.2x = -0.7 Add '-2.4' to each side of the equation. 2.4 + -2.4 + 2.2x = -0.7 + -2.4 Combine like terms: 2.4 + -2.4 = 0.0 0.0 + 2.2x = -0.7 + -2.4 2.2x = -0.7 + -2.4 Combine like terms: -0.7 + -2.4 = -3.1 2.2x = -3.1 Divide each side by '2.2'. x = -1.409090909 Simplifying x = -1.409090909
| 15x^3-9x^2+18x= | | 52-(2x+16)=2(x+3)+x | | 2(4x+5)=15 | | 6y+6=24 | | 392x-30-1=8x-4 | | x^2-51x=0 | | x-t=a+b | | 25x-9-12x+3=24x-4-11x+11 | | 7=8-1 | | s-t=t+x | | 2x+5=143 | | 5x+9-9x=15-17x+13x-6 | | 7m-28=28 | | N+26=41 | | a-b=x-g | | 3(y-2)= | | 5m+8=53 | | c-7=7 | | 300y=16500 | | 9r-10=46+r | | t-7=4 | | s+10=10 | | 2x^2+15x+18=a | | 9(t+2)=3(y-2) | | 2x^4+15=11x^2 | | 400x=200+x | | x^2+6x-18= | | M+3*2+3+7m=41 | | 3-2(x-2)=2(2-x) | | x^2=6x-18 | | 4(x-2)=2(x-4) | | 4t^6+8*t^3-32=0 |